Getting off the beaten path: Authentic assessments that enhance teaching, learning and academic integrity - Vogt, Lisa; Mercer, Brenda (Canadian Perspectives on Academic Integrity, 2022)
Getting off the beaten path will introduce participants to a variety of high-impact authentic assessment strategies to open the door for academic integrity to flourish. This session will begin by discussing the importance of aligning learning outcomes with authentic assessments to create space for diverse student experiences and abilities. From there we will explore a variety of hands-on learning approaches such as conferencing, collaboration, and refreshing your assignments to promote student engagement and realistic applications of course content. Participants in this session will learn how high-impact authentic assessment strategies may be embedded throughout planning, instruction, and assessment cycles. The strategies explored in this workshop will improve your course design by creating opportunities for your students to effectively and authentically demonstrate knowledge and skills. This session will culminate with a short group discussion on how course design with authentic assessment in mind, will naturally achieve much higher levels of academic integrity.